MODIFIKASI SISTEM PENDINGIN PADA MESIN DIESEL DARI TYPE HOPPER KE TYPE RADIATOR UNTUK MENINGKATKAN KINERJA PENDINGINAN - Lukman, Japri; Fiatno, Aris (Jurnal Teknik Industri Terintegrasi, 2019)
The engine cooling system is a system that functions to ensure engine temperature in ideal conditions. Diesel motor with hopper type cooling system, cooling effect is obtained by crawling the cylinder block heat into cooling water, causing the air to condense to the surface. To reduce the addition of hopper type cooling frequency, it was done to modify the hopper type cooling system to a radiator cooling system, the radiator cooling system is more effective in maintaining engine working temperature. The design of the cooling system is mounted parallel to the pulley, the cooling fan rotation is the same as the engine speed, while the radiator is installed in front of the cooling fan with the cooling fan distance to the radiator 13.5 cm. The thermostat speeds up the working temperature of the engine when the engine is still cold and also functions to maintain the engine always at work temperature. Operation of more than 1 hour of the hopper type cooling system needs to add water and the water temperature reaches 100 ° C past the intermediate working temperature of the machine (70 -80 ° C). In this condition, the type hopper cooling system does not normally maintain engine temperature for a long time because the engine temperature continues to increase, while the radiator cooling system will be stable at the working temperature